12q14 Microdeletions: Additional Case Series with Confirmation of a Macrocephaly Region. (22nd July 2015) - Mc Cormack, Adrian; Sharpe, Cynthia; Gregersen, Nerine; Smith, Warwick; Hayes, Ian; George, Alice M.; Love, Donald R.
Abstract : To date, there have been only a few reports of patients carrying a microdeletion in chromosome 12q14. These patients usually present with pre- and postnatal growth retardation, and developmental delay. Here we report on two additional patients with both genotype and phenotype differences. Similar to previously published cases, one patient has haploinsufficiency of the HMGA2 gene and shows severe short stature and developmental delay. The second patient is only one of a handful without the loss of the HMGA2 gene and shows a much better growth profile, but with absolute macrocephaly. This patient's deletion is unique and hence defines a likely macrocephaly locus that contributes to the general phenotype characterising the 12q14 syndrome.